Optimizing the sterilization methods for initiation of the five different clones of the Eucalyptus hybrid species. (November 2019) - Kuppusamy, Sowmya; Ramanathan, Seenivasan; Sengodagounder, Subramanian; Senniappan, Chinnaraj; Shanmuganathan, Rajasree; Brindhadevi, Kathirvel; Kaliannan, Thamaraiselvi
Abstract: In this study, five improved clones of the Eucalyptus hybrid species namely, E. pellita X E. camaldulensis (Clone No. 9), E. camaldulensis X E. pellita (Clone No. 21), E. camaldulensis X E. tereticornis (Clone No. 4), E. camaldulensis X E. p ellitta (Clone No. 16) and E. tereticornis X E. urophylla (Clone No. 41) were selected. The sterilization protocol were optimized and studied thoroughly for its contamination and survival rates. This aids in the micropropagation process of the five different clones of the Eucalyptus hybrid species. The nodal explants collected and stored were surface sterilized with different sterilizing agents namely, 70% Ethanol, 1% Sodium hypochlorite, 0.1% Mercuric chloride (HgCl2 ) and rifampicin (1 mg/mL) at different exposure period. Among the various sterilization methods tested, it was concluded that the best one was found to be with 0.1% HgCl2 for 3 min and rifampicin (1 mg/mL) for 5 min along with 1% sodium hypochlorite and 70% ethanol. The explants treated with this method showed higher survival rates in the plant cultures for all the five clones of the Eucalyptus hybrid species tested.